1970
DOI: 10.3329/jard.v4i1.770
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Whitefly Population Build up with the Spread of TYLCV on Eight Tomato Varieties

Abstract: The performance of eight tomato varieties namely BARI-T1 (Manik), BARI-T2 (Ratan), BARI-T4, BARI-T5, BARI-T6 (Apurba), BARI-T7 (Chaity), BARI-T11 and BARI-T12 were evaluated in respect to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
4
10
0
Order By: Relevance
“…The population of whitefly also depends on environmental factors like temperature, humidity and rainfall as also reported earlier (Rahman et al. , Islam et al. ).…”
Section: Discussionsupporting
confidence: 59%
“…The population of whitefly also depends on environmental factors like temperature, humidity and rainfall as also reported earlier (Rahman et al. , Islam et al. ).…”
Section: Discussionsupporting
confidence: 59%
“…This agrees with the positive correlation of whitefly population buildup in tomato fields with temperature that has been reported by Gupta (2000), Sultana (2001), Paul (2002), Haque (2002) and Parvin (2002). Rahman et al (2006) also reported a weak positive quadratic polynomial relationship between temperature and whitefly population build up in tomato fields. However, in the present study, significant relationship was not observed between virus disease incidence and the rainfall.…”
Section: Results Of Regression Analysismentioning
confidence: 94%
“…Rahman et al (2006), Mehta et al (1994), Gupta (2000), Paul (2002) and Parvin (2002) have reported an increase of whitefly population and its positive correlation with the spread of TYLCVD under field conditions. However, Ssekyewa et al (2007) reported that virus occurrence varied in space and time, and with management practices, crop development stage, and weather conditions based on field experiments conducted on TYLCV and tomato leaf curl virus (ToLCV) using two crop management systems (i.e.…”
Section: Results Of Regression Analysismentioning
confidence: 97%
See 2 more Smart Citations